The Influence Of Work Ability And Teamwork On Employee Performance At Pt. Nauli Jaya Persada - Rukhayati; Abdul Rahman; I Made OFayana (Fakultas Ekonomi Universitas Muhammadiyah Palu, 2024)
This study aims to analyse the effect of work ability and cooperation on employee performance at PT Nauli Jaya Persada. The method used is multiple linear regression analysis to test the relationship between the independent variable (work ability and cooperation) and the dependent variable (employee performance). A total of 40 respondents from PT Nauli Jaya Persada. The results showed that work ability has a significant positive effect on employee performance. This shows that by improving work ability, employees can achieve better performance. In addition, this study also found that cooperation has a significant positive effect on employee performance. With good cooperation between employees, they can work effectively and efficiently, which in turn improves their performance.